HUBUNGAN KOORDINAS MATA TANGAN TERHADAP KETERAMPILAN PASSING ATAS SISWA SMP NEGERI 1 LEBONG UTARA KABUPATEN LEBONG - Feby Elra Perdima (Universitas Negeri Medan, 2018)
Based on the observation in the field it shows that still lack of agility of ability eyes and hands coordination to passing skill student at SMP N 1 Lebong. This study aims to explain the relationship of eyes and hands coordination to the passing skill student at SMP N 1 Lebong. This research method used is correlation, with the population of this study a number of 17 athletes and samples taken by using the total sampling technique so that obtained a sample of 17 athletes. Eyes and hands coordination test and passing skill used product moment. The result of analysis shows that there is relationship between eyes and hands coordination to the passing skill is 0.78.